Marulić i petrarkizam - Bogdan, Tomislav (Array, 2002)
The study of Marulić's works, particularly those in the Croatian language, has revealed elements of Petrarchistic discourse. The author poses the question of the manner in which they were used, particularly since the forms they take at different levels (motifs, metaphors) and the types of expression carrying them clearly show that Marulić was alien to the Petrarchistic treatment of amorous situations. Unlike the authors of secular Petrarchistic poetry, in whose songs the aesthetic achieves emancipation at the thematic level, Marulić manipulates the concept of woman's beauty and compels the elements of Petrarchistic discourse to serve his particular religious and didactic scopes.